Probing gravitational fluctuations in spherically symmetric black holes and extreme mass ratios systems - Lucchini, André Felipe Moraes Luiz [UNESP] (2024)
Einstein’s theory of General Relativity transformed our understanding of gravity by predicting the existence of black holes—astrophysical objects with gravitational fields so strong that not even light can escape. Over time, theoretical developments and astronomical observations have established black holes as key phenomena in modern astrophysics, particularly in the study of Extreme Mass Ratio Inspirals (EMRs), where a supermassive black hole interacts with a much smaller compact object. These systems are vital for testing the predictions of General Relativity, as they generate gravitational waves that encode detailed information about the properties of the black hole and the surrounding spacetime. This master thesis reviews the literature on gravitational perturbations emitted by black holes, examining the emergence of quasi-normal modes (QNMs) and their role in dissipating energy via gravitational waves. Furthermore, it shows the dynamics of radial infall in Schwarzschild black holes and the application of perturbative methods in Kerr spacetime to explore gravitational self-force effects in EMRIs, reviewing into it orbital evolution and dissipative mechanisms.